Differences in HIV-related behaviors among MSM college/university students with different sexual orientations: a cross-sectional survey in Zhejiang province - Lin CHEN; Jie XU; Wanjun CHEN; Yun XU; Lin HE; Chengliang CHAI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo examine differences in HIV-related behaviors among college students who are men who have sex with men (MSM) and of different sexual orientations. MethodsA total of 682 MSM students aged ≥18 years were recruited from colleges/universities in four cities (Hangzhou, Ningbo, Jiaxing and Jinhua) in Zhejiang province through convenience sampling with the help of NGO (non-governmental organization) for a web-based on-site survey with face-to-face instructions from interviewers from March to July 2022. Participants' information on household registration, campus location, years in college, public expression of sexual identity, online casual sex, substance abuse, HIV knowledge, pre-exposure and post-exposure prophylaxis, and HIV testing were collected using a self-compiled questionnaire. SPSS 25.0 software was used for data analysis. ResultsOf the 671 valid respondents, 73.3% reported a homosexual orientation and 26.7% reported a bisexual/unsure orientation. Compared to respondents with a homosexual orientation, respondents with a bisexual/uncertain orientation reported significantly lower rates of publicly expressing their sexual identity (50.8% vs. 60.2%), receiving health education about condom use from peers (70.9% vs. 79.1%), and self-testing for HIV once or more (64. 4% vs. 76.0%), but significantly higher rates of first homosexual behavior within the past year (48.8% vs. 37.4%), being seduced or coerced into first homosexual behavior (27.4% vs. 16.5%), and using sex-stimulating rush popper during their last online casual sexual encounter (40.7% vs. 27.1%) (P < 0.05 for all). ConclusionThere are significant differences between MSM college/university students with a homosexual orientation and those with a bisexual/unsure orientation in public expression of sexual identity, timing and type of first homosexual encounter, use of rush popper and other substances, receipt of peer education about condom use, and self-testing for HIV, suggesting that targeted interventions to reduce the risk of HIV infection in this population should be strengthened.